Detection of polyphosphates in seafood and its relevance toward food safety. (1st December 2020) - Panseri, Sara; Arioli, Francesco; Biolatti, Cristina; Mosconi, Giacomo; Pavlovic, Radmila; Chiesa, Luca Maria
Highlights: HPIEC-SCD- high-resolution mass spectrometry (HRMS) for polyphosphates profiling. HRMS proposed new linear/cyclic polyphosphates forms specific for food control. HPIEC-SCD-HRMS platform revealed hexametapolyphosphate in some fishery products. Abstract: Polyphosphates are permitted as food additives (Regulation EC No 1129/2011) but their undeclared utilisation is considered fraudulent. They improve water holding capacity of the seafood, preventing biochemical/physical changes during commercialization. The key objective of this study was the detection of polyphosphate in various seafood categories, by means of high-performance ion-exchange chromatography with suppressed conductometry (HPIEC-SCD) coupled to Q-Exactive Orbitrap high resolution mass spectrometry (HRMS-Orbitrap). Ten frozen cuttlefish samples did not reveal any treatment, while in ten frigate tunas, high concentration of orthophospate was found. Unambiguous hexametaphosphate presence was demonstrated in four prawn samples, while triphosphate was quantified (11.2 ± 4 ug/g) in another four prawn samples that contained orthophosphate (10225 ± 1102 ug/g), as well. Other samples sporadically encompassed polyphosphates profiles that varied according species and processing type. This analytical approach provided sustenance in better understanding regarding utilization of polyphosphates through HRMS fingerprinting of anionic species that would be specific in food safety control.